Unrecognized Hornets’ Nests of Basic Contract Law - Does the Law Permit a Seller to Offer the Same Item to Two or More Buyers Under Bilateral Contracts? - Palawatta Dinushi Tennekoon (Journal of Legal Studies)
The law of contracts stands as a mechanism for creating and enforcing legal rights and obligations that ensure that parties are held to their respective promises. However, if contract law permits a seller to agree to sell the same item to two or more buyers to the extent of creating two valid contracts, this may violate one of the main purposes of contract law which is to bring certainty and predictability pertaining to the duties and rights of the parties. This article initially examined the elements of contract law to analyze if the same could give rise to two or more valid bilateral agreements purporting to sell the same item to different individuals. This was followed by proposed reforms to the existing framework to protect both sellers and buyers who may not be aware of the legal framework governing their relationships. After assessing and evaluating whether a seller of limited stocks can contract to sell more than they own, it was identified that it is legally possible for a seller to be bound by two or more valid contracts to sell the same item. It was proposed to either interpret the expression of willingness to sell a product by a seller with limited stocks as an invitation to treat or subject the validity of concepts of offer and acceptance to the condition of availability of stocks as mechanisms to afford protection to domestic sellers who may be incautious of the surrounding legal rules.